Women's experiences of more than one termination of pregnancy within two years: a mixed‐methods study. (20th October 2017) - Purcell, C; Riddell, J; Brown, A; Cameron, ST; Melville, C; Flett, G; Bhushan, Y; McDaid, L
Abstract : Objective: To examine the experiences of women seeking more than one termination of pregnancy (TOP) within 2 years. Design: Mixed methods study. Setting: Six TOP services across Scotland. Sample: Women presenting for TOP between July and December 2015. Methods: Descriptive and inferential analysis of quantitative survey data, thematic analysis of qualitative interview data and integrative analysis. In quantitative analysis, multinomial logistic regression was used to compare three groups: previous TOP within 2 years, previous TOP beyond 2 years and no previous TOP. Main outcome measures: Characteristics and experiences of women seeking TOP. Results: Of 1662 questionnaire respondents, 14.6% ( n = 242) and 19.8% ( n = 329) reported previous TOP within and beyond 2 years, respectively. The previous TOP within 2 years group was significantly less likely to own their accommodation than the no previous TOP group (adjusted odds ratio [aOR] 0.34, 95% CI: 0.18–0.62) and previous TOP beyond 2 years group (aOR: 0.44, 95% CI: 0.23–0.85); and more likely to report inconsistent (aOR: 1.63, 95% CI: 1.04–2.57; aOR: 1.95, 95% CI: 1.16–3.28) and consistent (aOR: 2.13, 95% CI: 1.39–3.26; aOR: 1.71, 95% CI: 1.07–2.76) contraceptive use than the no previous TOP and previous TOP within 2 years groups, respectively. Twenty‐three women from the previous TOP within 2 years group were interviewed. Qualitative and integrative analyses highlight issues relating to contraceptive challenges, intimate partner violence, life aspirations and socio‐economic disadvantage. Conclusions: Women undergoing more than one TOP within 2 years may experience particular challenges and vulnerabilities. Service provision should recognise this and move away from stigmatising discourses of 'repeat abortion'. Funding: Scottish Government. Tweetable abstract: Women having two or more terminations of pregnancy in 2 years may face key challenges/vulnerabilities including intimate partner violence and socio‐economic disadvantage. Tweetable abstract: Women having two or more terminations of pregnancy in 2 years may face key challenges/vulnerabilities including intimate partner violence and socio‐economic disadvantage.